2014
DOI: 10.4028/www.scientific.net/amr.1040.455
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Plasticity Modeling of Duplex Steels at High Temperatures

Abstract: The paper considers physical approach to the description of inelastic deformation of two-phase polycrystalline materials – duplex steels. Such approach is based on the introduction the key mechanisms of inelastic deformation in explicit way. The main mechanism of plastic deformation is slipping of edge dislocations. The structure of duplex steel consists of austenite and ferrite phases. At high temperatures ferrite reveals dynamic recovery (DRV) and austenite ability to undergo dynamic recrystallization (DRX).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The complexity increases because of the simultaneous presence of δ and γ phases in DSS. Some reports have indicated that the ferrite phase of DSS exhibits dynamic recovery (DRV) at high temperatures, and the austenite phase of DSS dynamic recrystallization (DRX) [29,30]. Because γ has a lower yield stress than δ in DSS, thermal stress-induced plastic deformation occurred earlier at the γ grains.…”
Section: Misorientation Angle Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity increases because of the simultaneous presence of δ and γ phases in DSS. Some reports have indicated that the ferrite phase of DSS exhibits dynamic recovery (DRV) at high temperatures, and the austenite phase of DSS dynamic recrystallization (DRX) [29,30]. Because γ has a lower yield stress than δ in DSS, thermal stress-induced plastic deformation occurred earlier at the γ grains.…”
Section: Misorientation Angle Analysismentioning
confidence: 99%
“…The degree of local crystalline misorientation within each grain was determined by the illustrated color-typed code. Red (5 • ) corresponds to the highest misorientation, whereas blue (0 • ) corresponds to the grains without any misorientation [29]. In Figure 7, the KAM maps show the misorientation at the interfaces between the γ, δ, and σ phases, in an order of the as-received (Figure 7a), 2SS (Figure 7b), 2SS + 3 cycles (Figure 7c), 2SS + 7 cycles (Figure 7d), 2SS + 13 cycles (Figure 7e), and 2SS + 20 cycles (Figure 7f) from 0 • to 5 • .…”
Section: Kernel Average Misorientation (Kam) Analysismentioning
confidence: 99%
See 1 more Smart Citation